Microstructure and Texture of Hydrostatic Extrusion Deformed Ni Single Crystals and Polycrystal. (7th September 2015) - Jakubowska, D.; Zdunek, J.; Kulczyk, M.; Mizera, J.; Kurzydłowski, K. J.
Abstract : The differences in the microstructure and texture of two Ni single crystals, with different initial orientations (100 and 110 ), and of polycrystalline nickel, before and after severe plastic deformation (SPD) produced by hydrostatic extrusion (HE), have been investigated. The crystals were deformed by a two-step HE process with a total deformation value of ε = 1.2 . The global texture, mechanical properties, and microstructure were examined after the deformation. In every investigated sample, the presence of 111 fibre texture was noted, while the starting orientation of a 100 Ni single crystal was preserved in 50% of the volume. The results obtained were compared with the relevant literature data.